La imagen de la profesión proyección de la autoimagen sexual-profesional - Brignardello, Luisa A. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Results of the content analysis of the answers of 100 psychology and sociology university students to the open-ended question: ‘‘What is the role of the social psychologist in society?” are presented. Three independent variables — career, sex and age — and their interactions were examined. The answers were analyzed in terms of the following categories: action and quality; and connotation of the action and of the quality (passive-active, positive-negative). The perceptions of the role as it should be, the assignment of responsibility to the individual o r to society, and total o t partial conditioning of the role were also studied as dependent variables.